Transzygomatic Approach with Intraoperative Neuromonitoring for Resection of Middle Cranial Fossa Tumors - Son, Byung Chul; Lee, Sang Won, II; Kim, Sup; Hong, Jae Taek; Sung, Jae Hoon; Yang, Seung-Ho (Journal of Neurological Surgery Part B: Skull Base, 2012)
The authors reviewed the surgical experience and operative technique in a series of 11 patients with middle fossa tumors who underwent surgery using the transzygomatic approach and intraoperative neuromonitoring (IOM) at a single institution. This approach was applied to trigeminal schwannomas (n = 3), cavernous angiomas (n = 3), sphenoid wing meningiomas (n = 3), a petroclival meningioma (n = 1), and a hemangiopericytoma (n = 1). An osteotomy of the zygoma, a low-positioned frontotemporal craniotomy, removal of the remaining squamous temporal bone, and extradural drilling of the sphenoid wing made a flat trajectory to the skull base. Total resection was achieved in 9 of 11 patients. Significant motor pathway damage can be avoided using a change in motor-evoked potentials as an early warning sign. Four patients experienced cranial nerve palsies postoperatively, even though free-running electromyography of cranial nerves showed normal responses during the surgical procedure. A simple transzygomatic approach provides a wide surgical corridor for accessing the cavernous sinus, petrous apex, and subtemporal regions. Knowledge of the middle fossa structures is essential for anatomic orientation and avoiding injuries to neurovascular structures, although a neuronavigation system and IOM helps orient neurosurgeons.
Keywords: middle fossa approach; skull base surgery; motor-evoked potentials; intraoperative monitoring; neurophysiology